Septicemia detection by blood buffy coat smear in primary health care centers - Jha, BK; Singh, YI; Mahadevmurthy, S; Chaudhary, NK (Journal of College of Medical Sciences-Nepal, 2012)
Early diagnosis of childhood septicemia can be done by simple tests like C-reactive protein (CRP) and anticoagulant added blood centrifuged buffy coat smear (BBCS) examination, where there is no well equipped hospital setting for blood culture and identification facility in remote health care centers. This study was conducted between 1st Jan. 2007 to 27th Dec. 2007 in College of Medical Sciences, Bharatpur, Nepal. In this study we have selected 150 suspected cases of childhood septicemia for screening CRP by kit method and BBCS by two slide techniques. This kit is supplied by Span Diagnostic Pvt. Ltd. (Surat, India). Out of 150 cases of childhood septicemia of age group 0-14 years, 83 had positive C- reactive protein (CRP >6ì g/ml), 70 were positive for BBCS and blood culture was positive only in 83 cases, where predominant organism being Klebsiella species followed by Staphylococcus species. CRP test showed 100.0% sensitivity and 87.30% specificity, where BBCS showed 76.5% sensitivity and 91.2% specificity. Blood culture reports are available only after 48-72 hours and this facility is available only in well equipped centers but CRP and BBCS are easy and cheap procedure to perform even in remote areas for early diagnosis of childhood septicemia. DOI: http://dx.doi.org/10.3126/jcmsn.v7i1.5968 JCMSN 2011; 7(1): 19-23